LEXICAL STYLISTIC DEVICES: METAPHOR, METONYMY, IRONY, POLYSEMY, AND EPITHET (Ustozlar uchun, 2026)
This article examines the fundamental lexical stylistic devices outlined in the fourth point of the stylistics curriculum: metaphor, metonymy, irony, polysemy, and epithet. It provides definitions, analyzes their functions, and explains the mechanisms through which they impact the reader. The article emphasizes the crucial role these tropes play in creating imagery, expressiveness, and conveying subtext in both literary and publicistic texts.